FINANCIAL PERFORMANCE MEDIATES THE EFFECT OF GOOD GOVERNANCE ON COMPANY VALUE IN INDONESIAN MANUFACTURING COMPANIES - Riska Yanti; Nazariah Nazariah; Ramzijah Ramzijah; Arina Nurfaza; Evi Maulida Yanti (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study is a quantitative study to assess financial performance mediating the influence of good governance on the value of manufacturing companies in Indonesia, the food & beverage sub-sector manufacturing listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population of manufacturing companies in the food and beverage sub-sector listed on the IDX in 2019-2023 is 102 companies, but only 23 companies meet the criteria and requirements that publish their financial reports consecutively. Data processing uses the EViews application. The results of the study indicate that good governance has an effect on company value, good governance does not affect financial performance value, and financial performance does not affect company value. And financial performance is unable to mediate the influence of effective governance on company value. Keywords: Financial Performance; Good Governance; Company Value